Study on the influence of Party organization climate on college students’ ideological, political and behavioral patterns and countermeasures based on Apriori algorithm - Han, Sufang; Wang, Shenghan (International Journal of Computer Science and Information Technology, 2023)
When the organizational climate refers to the group atmosphere, it directly influences and dominates the subjective psychological factors shaped by the subjective environment of the organization’s target. The excellent organizational climate also determines the effect of the group. Taking the climate of Party organizations as the starting point and students of Yunnan Minzu University as the research carrier, this paper introduces the "climate" of party organizations into its influence on ideology, politics and behavior patterns, reflecting the analogical discussion of the entity form of "climate" in the aspects of party organization system construction, psychological compatibility degree and mode of action. The Apriori correlation algorithm is used to match attitude, thought, spirit and behavior, which are persistent and interact with each other, with climate, and which party organization climate factors have a deep impact on college students’ ideological, political and behavioral patterns? In particular, the influence and degree of the party organization climate on the transformation of students’ employment concept are also investigated and quantitatively analyzed, and the countermeasures of the influence of the Party organization climate on the ideological, political and behavioral patterns of college students are found.